Study on the compatibility of modified cyanate ester resin in liquid oxygen. (12th September 2020) - Fu, Gang; Jiao, Weicheng; Wang, Guan; Gao, Tanling; Wu, Jianwei; Shao, Nan; Wei, Yun Zhao; Kuang, Hong; He, Xiaodong; Wang, Rongguo
Abstract: A cyanate ester (CE) resin co‐modified with epoxy (EP) and bismaleimide (BMI) as the continuous phase, and phenolphthalein poly (ether sulfone) (PES‐C) as the dispersed phase were used for developing liquid oxygen (LOX) composite tanks. Gaseous oxygen (GOX) anti‐oxidation, LOX impact sensitivity, ductility, and cycle durability is a critical index for materials in LOX applications. Added components significantly improved material ductility at low temperature versus neat CE resin because of microstructure changes. However, improvement in thermal resistance was not achieved without tradeoffs; the addition of BMI improved thermal resistance but decreased durability. The failure mechanism of a tank containing GOX was related to reaction with oxygen. LOX impact sensitivity (IRS) is associated with anti‐oxidation and flaming retardance of the samples. Micro‐domains tended to separate from the continuous phase more during the LOX impact test versus the GOX test and was accompanied by increasing ductility and anti‐oxidation. Cycle durability was affected more by the difference in coefficient of thermal expansion between the continuous and PES‐C phases rather than immersion time. In summary, CE resin (CYEP6BM5) co‐modified with PES‐C, EP, and BMI showed good LOX compatibility including IRS value of 2%, 19 cycles durability, and flaming retardance of UL94V0 and may be applied for LOX composite tanks. Abstract :